2021
DOI: 10.3390/microorganisms9091812
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Resolved Meta-Analysis of the Microbiome in Oil Reservoirs Worldwide

Abstract: Microorganisms inhabiting subsurface petroleum reservoirs are key players in biochemical transformations. The interactions of microbial communities in these environments are highly complex and still poorly understood. This work aimed to assess publicly available metagenomes from oil reservoirs and implement a robust pipeline of genome-resolved metagenomics to decipher metabolic and taxonomic profiles of petroleum reservoirs worldwide. Analysis of 301.2 Gb of metagenomic information derived from heavily flooded… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 114 publications
2
10
0
Order By: Relevance
“…4 ). These results are consistent with observations of high proportions of genes for enzymes involved in aerobic hydrocarbon metabolism in various anaerobic hydrocarbon resource environments including oil reservoirs ( 29 , 49 ) and may arise from the enrichment of initially minor groups of organisms capable of aerobic respiration coming into contact with air during sampling and sample transport. This is substantiated by genes encoding alkane hydroxylase ( alkB ) and monoaromatic dioxygenase (MAH) showing high-sequence identity (based on BLAST against the nonredundant nucleotide database) with Marinobacter spp., which are generally detected in low relative abundance in situ by 16S rRNA gene amplicon sequencing ( Table S5 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…4 ). These results are consistent with observations of high proportions of genes for enzymes involved in aerobic hydrocarbon metabolism in various anaerobic hydrocarbon resource environments including oil reservoirs ( 29 , 49 ) and may arise from the enrichment of initially minor groups of organisms capable of aerobic respiration coming into contact with air during sampling and sample transport. This is substantiated by genes encoding alkane hydroxylase ( alkB ) and monoaromatic dioxygenase (MAH) showing high-sequence identity (based on BLAST against the nonredundant nucleotide database) with Marinobacter spp., which are generally detected in low relative abundance in situ by 16S rRNA gene amplicon sequencing ( Table S5 ).…”
Section: Discussionsupporting
confidence: 91%
“…The hydrocarbon activation genes assA , bssA , and nmsA were only detected in one-quarter of the oil reservoirs examined by metagenome sequencing in this study. A similar result was reported by Hidalgo et al ( 29 ) who found only two bssA genes in 148 MAGs from different oil reservoirs using KEGG assignments. The discrepancy of widespread genomic potential for methanogenesis and geochemical evidence of biogenic methane production in reservoirs ( 37 , 38 ) on the one hand, and limited occurrences of anaerobic hydrocarbon degradation genes on the other, hints that other mechanisms for anaerobic hydrocarbon biodegradation ( 39 41 ) or as-yet undetected hydrocarbon activation genes in anoxic petroleum reservoirs.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This phylum is characterized by small cell and genome sizes(Tian et al 2020;Hidalgo et al 2021), carrying only essential genes and lacking a lot of metabolic functions(Hidalgo et al 2021;Brown et al 2015). For this reason, some authors have proposed that members of this phylum have a symbiont lifestyle(Castelle et al 2018;Hidalgo et al 2021).…”
mentioning
confidence: 99%